2012
DOI: 10.4172/2153-2435.1000180
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Salmeterol Xinafoate and Fluticasone Propionate in Bulk Powder and SeritideDiskus using High Performance Liquid Chromatographic and Spectrophotometric Method

Abstract: Five methods were developed for simultaneous determination of Salmeterol xinafoate (SAM) and Fluticasone propionate (FLU) without previous separation. In the first method (HPLC), a reversed-phase column and a mobile phase of acetonitrile: methanol (80:20 v/v) at 0.5 mLmin-1 flow rate was used to separate both drugs and UV detection at 220 nm. Linearity was obtained in concentration ranges of 50-500 µgmL-1 for Salmeterol xinafoate Fluticasone propionate. In the second method both drugs were determined using fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…For example, in a previous study, an X-terra column (250 mm x 4.6 mm, 5 µm) was used to elute FP and SX with mobile phase consisted of Methanol: Acetonitrile: Water (50:35:15 % v/v) at 1 ml/min flow rate [12]. In other reported methods Acetonitrile: Methanol, Methanol: Water, buffered or modified mobile phases with different types of columns were used [9,11,26,[28][29][30][31][32].…”
Section: Methods Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a previous study, an X-terra column (250 mm x 4.6 mm, 5 µm) was used to elute FP and SX with mobile phase consisted of Methanol: Acetonitrile: Water (50:35:15 % v/v) at 1 ml/min flow rate [12]. In other reported methods Acetonitrile: Methanol, Methanol: Water, buffered or modified mobile phases with different types of columns were used [9,11,26,[28][29][30][31][32].…”
Section: Methods Optimizationmentioning
confidence: 99%
“…Several chromatographic techniques have been published in the literature for analysis purposes of fluticasone propionate (FP) and/or, salmeterol xinafoate (SX) in their pharmaceutical preparations and different matrices. For example these methods include UVspectrometric methods [6,7], HPLC with UV detection methods [8][9][10][11][12][13], HPLC-MS/MS methods [14,15], UPLC-MS/MS methods [16,17], UPLC-PDA method [18], and HPTLC method [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing the literature revealed that different analytical methods were established for determination of FLP and AZH either alone or in combination. These methods include: spectrophotometry [5][6][7][8][9][10][11][12], spectrofluorometry [13,14], electrochemical methods [15][16][17], TLC [18,19], HPLC [5,11,[20][21][22][23][24][25][26][27][28][29]] HPTLC [30][31][32], LC/MS/MS [33][34][35][36][37][38][39] and capillary electrophoresis [40,41]. It was found that only two spectrophotometric methods [42,43] and two HPLC methods [44,45] were reported for quantification of the binary mixture of FLP and AZH.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the methods with LLOQ above 0.1 μg mL −1 are not suitable for monitoring the invitro deposition pattern. Moreover, in some methods, the quantitation limit had not been provided [6] or only theoretical values of detection limits calculation, based on the standard, were assessed [7]. The methods involving spectrophotometry are widely used in pharmaceutical control laboratories due to their simplicity, low-cost instrumentation, and adaptability.…”
Section: Introductionmentioning
confidence: 99%
“…Few high-performance liquid chromatography (HPLC) analytical methods have been published so far for SX and FP simultaneous determination in pharmaceutical formulation [3][4][5][6][7]. According to the International Conference on Harmonization guidelines, if a value for the detection limit is obtained by calculation or extrapolation, this estimate should be subsequently validated by an independent analysis of a suitable number of samples known to be near or at the detection limit which has not been the case so far [8].…”
Section: Introductionmentioning
confidence: 99%